Some cardiopulmonary effects of capnoperitoneum in anesthetized guinea pigs (Cavia porcellus): spontaneous ventilation versus intubation and mechanical ventilation. (January 2023) - McCready, Julianne E.; Sanchez, Andrea; Tisotti, Tainor; Beaufrère, Hugues
Abstract: Objective: To compare cardiopulmonary variables and blood gas analytes in guinea pigs ( Cavia porcellus ) during anesthesia with and without abdominal carbon dioxide (CO2 ) insufflation at intra-abdominal pressures (IAPs) 4 and 6 mmHg, with and without endotracheal intubation. Study design: Prospective experimental trial. Animals: A total of six intact female Hartley guinea pigs. Methods: A crossover study with sequence randomization for IAP and intubation status was used. The animals were sedated with intramuscular midazolam (1.5 mg kg –1 ) and buprenorphine (0.2 mg kg –1 ) and anesthetized with isoflurane, and an abdominal catheter was inserted for CO2 insufflation. Animals with endotracheal intubation were mechanically ventilated and animals maintained using a facemask breathed spontaneously. After 15 minutes of insufflation, the following variables were obtained at each IAP: pulse rate, respiratory rate, rectal temperature, oxygen saturation, end-tidal CO2 (intubated only), peak inspiratory pressure (intubated only), noninvasive blood pressure and blood gas and electrolyte values, with a rest period of 5 minutes between consecutive IAPs. After 4 weeks, the procedure was repeated with the guinea pigs assigned the opposite intubation status. Results: Intubated guinea pigs had significantly higher pH and lower partial pressure of CO2 in cranial vena cava blood (PvCO2 ) than nonintubated guinea pigs. An IAP of 6 mmHg resulted in a significantly higher PvCO2 (65.9 ± 19.0 mmHg; 8.8 ± 2.5 kPa) than at 0 (53.2 ± 17.2 mmHg; 7.1 ± 2.3 kPa) and 4 mmHg (52.6 ± 10.8 mmHg; 7.01 ± 1.4 kPa), mean ± standard deviation, with intubated and nonintubated animals combined. Conclusions and clinical relevance: Although the oral anatomy of guinea pigs makes endotracheal intubation difficult, capnoperitoneum during anesthesia induces marked hypercapnia in the absence of mechanical ventilation. An IAP of 4 mmHg should be further evaluated for laparoscopic procedures in guinea pigs because hypercapnia may be less severe than with 6 mmHg.